2015
DOI: 10.1183/16000617.00004114
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experience and asthma onset: a systematic review

Abstract: Adverse childhood experiences such as abuse and neglect are associated with subsequent immune dysregulation. Some studies show an association between adverse childhood experiences and asthma onset, although significant disparity in results exists in the published literature.We aimed to review available studies employing a prospective design that investigates associations between adverse childhood experience and asthma. A search protocol was developed and studies were drawn from four electronic journal database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 25 publications
7
46
0
1
Order By: Relevance
“…35 Our intergenerational findings for offspring health outcomes mirror existing research linking ACEs with poorer health in the same individuals, PEDIATRICS Volume 141, number 6, June 2018 5 including obesity and asthma. 1,2,5,36,37 ACEs have also been related to poor self-rated health status among adults, although this has not been the case in 2 recent studies of youth. 1,38,39 Pediatric research shows withinindividual associations between child ACE exposure and poorer physical, psychological, and developmental health.…”
Section: Discussionmentioning
confidence: 93%
“…35 Our intergenerational findings for offspring health outcomes mirror existing research linking ACEs with poorer health in the same individuals, PEDIATRICS Volume 141, number 6, June 2018 5 including obesity and asthma. 1,2,5,36,37 ACEs have also been related to poor self-rated health status among adults, although this has not been the case in 2 recent studies of youth. 1,38,39 Pediatric research shows withinindividual associations between child ACE exposure and poorer physical, psychological, and developmental health.…”
Section: Discussionmentioning
confidence: 93%
“…An association between childhood maltreatment and sexual revictimization in adult life was indeed established in general population studies for both women and men (Werner et al, 2016;Fergusson et al, 1997;Roodman and Clum, 2001;Desai et al, 2002;Filipas and Ullman, 2006). ACE seem to influence the immune system and to be associated with the onset of asthma in children (Exley et al, 2015). Other chronic medical conditions might be associated as well.…”
Section: Introductionmentioning
confidence: 87%
“…In particular, there has been a great amount of research on how childhood socioeconomic status (CSES) and childhood abuse (CA) relate to chronic conditions in later life, and reviews have shown reasonable associations between these variables (Kalmakis and Chandler 2015;Pavalko and Caputo 2013;Spencer et al 2013). Several previous studies have consistently shown that childhood adversities are associated with asthma (Exley et al 2015), bronchitis (Springer et al 2007), hypothyroid (Post et al 2013), migraine (Post et al 2013), and psychiatric disorders (Sheikh et al 2014;Sheikh et al 2016a;Sheikh et al 2016b) in later life.…”
Section: Introductionmentioning
confidence: 99%